Effect of Opuntia ficus-indica (L.) Mill. Cladodes in the Wound-Healing Process (Journal of the Professional Association for Cactus Development, 2003)
Opuntia ficus-indica (L.) Mill. cladodes contain a polysaccharide fraction that can retain water. The cladodes are used in Sicilian folk medicine as cicatrizant. We studied the healing activity of a base cream containing 15% lyophilized cladodes and of a commercial ointment on the wound produced on the backs of rats. The treatment was carried out for 3 and 5 days. After three days of treatment, the scar tissue is evident, both fibers and fibroblasts in the derma are properly arranged. The dermal vessels are reduced in lumen and the keratinocytes show proliferation areas. In the 5 days' treatment, the wound healing process is almost completed and the piliferous bulbs are recovering. Complete epithelization occurs. Evidently, the O. ficus-indica treatment accelerates wound healing, probably by involving the proliferation and migration of the keratinocytes in the healing process.